Neutrinoless Double β+/EC Decays - Jukka Maalampi; Jouni Suhonen (Advances in High Energy Physics)
The relation of neutrino masses to neutrino oscillations and the nuclear double beta decay is highlighted. In particular, the neutrinoless β+β+, β+EC, and resonant ECEC decays are investigated using microscopic nuclear models. Transitions to the ground state and excited 0+ states are analyzed. Systematics of the related nuclear matrix elements are studied and the present status of the resonant ECEC decays is reviewed.